Orthodontic camouflage versus orthodontic-orthognathic surgical treatment in class II malocclusion: a systematic review and meta-analysis - Raposo, R (2017)
This systematic review was performed to compare dental, skeletal, and aesthetic outcomes between orthodontic camouflage and surgical-orthodontic treatment, in patients with a skeletal class II malocclusion and a retrognathic mandible who have already finished their growth period. A literature search was conducted, and a modified Downs and Black checklist was used to assess methodological quality. The meta-analysis was conducted using the DerSimonian–Laird random-effects method to obtain summary estimates of the standardized mean differences and corresponding 95% confidence intervals. Nine articles were included in the qualitative synthesis and seven in the meta-analysis. The difference between treatments was not statistically significant regarding SNA angle, linear measurement of the lower lip to Ricketts’ aesthetic line, convexity of the skeletal profile, or the soft tissue profile excluding the nose. In contrast, surgical-orthodontic treatment was more effective with regard to ANB, SNB, and ML/NSL angles and the soft tissue profile including the nose. Different treatment effects on overjet and overbite were found according to the severity of the initial values. These results should be interpreted with caution, due to the limited number of studies included and because they were non-randomized clinical trials. Further studies with larger sample sizes and similar pre-treatment conditions are needed.